تقويم منهج تعليم اللغة العربية في معهد الإصلاح بجاوا الشرقية إندونيسيا - Adhib Kurniawan (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This study aims to evaluate the implementation of the Arabic language curriculum at al-Islah Islamic Boarding School in East Java, Indonesia. It employs descriptive and evaluative methods and it consist of two parts: theoretical and practical. The theoretical part discusses the school's Arabic language Curriculum. It also explains the evaluation elements of the Arabic teaching curriculum towards non-native speakers as used in this research. The practical part introduces the researcher's evaluations based on the conducted field study where researcher studied the basic references, analysed the interview with the school's director and language sectionsas well as the results of the questionnaire distributed to teachers and leaners. The observations made to the circle of the school helps improving the validity of the results. The results suggest two landmark points. Firstly, the school implements a direct method in Arabic language teaching. Secondly, Arabic is used as the medium of instruction in all Islamic studies as well as in circles's activities.